Access to trans‐3, 4‐Dihydroxy‐2‐alkylpyrrolidines and Piperidines by Use of Stereodefined Cyclic N, O‐Acetals as a Diversity‐Generating Element. Issue 49 (13th October 2014) - Kang, Soyeong; Kim, Dong‐gil; Rhee, Young Ho
Abstract A highly efficient and stereoselective synthetic pathway towards trans‐3, 4‐dihydroxy‐2‐alkylpyrrolidines and piperidines is described. The nature of the protecting groups on the hydroxyl moieties played a crucial role on the trans selectivity. By using this method, a concise total synthesis of (−)‐2‐epilentiginosine has been achieved.